Farming Households' Satisfaction With Quality of Agricultural Extension Services: A Case Study of Quang Binh Province, Vietnam - Truong, Dinh Duc (Frontiers in Sustainable Food Systems, 2022)
Agriculture is an important sector of Vietnam, in which agricultural extension (AE) is a long-standing activity but was officially institutionalized in 1993 when Vietnam reformed its economic model. The AE system in Vietnam is organized quite closely from the central to local levels with various forms of AE. This study assesses the satisfaction of farmers with AE services in Quang Binh province, Vietnam. The results of a survey of 455 farmers show a positive relationship between quality and satisfaction. Factors such as assurance, reliability, and sympathy are important factors in AE service quality. The study also provides recommendations to strengthen AE services, including updating technical information, organizing demonstration models, and stronger investment in AE systems at all levels.